Fabrication of microcompartments with controlled size and shape for encapsulating active matter - Vianay, Benoit; Guérin, Christophe; Gressin, Laurène; Orhant-Prioux, Magali; Blanchoin, Laurent; Théry, Manuel; Colin, Alexandra (Frontiers in Cell and Developmental Biology, 2025)
In all living systems, the cytoplasm is separated from the external environment by membranes. This confinement imposes spatial constraints on the self-organization of internal components, filaments and organelles. While reconstituted systems are instrumental for understanding fundamental biological principles, traditional experiments often utilize volumes vastly larger than actual cells. In recent studies, water-in-oil droplets or giant unilamellar vesicles have been widely used to impose confinement. However, these compartments present imaging challenges and make precise protein content control difficult. To address these limitations, we have developed versatile microwells that are straightforward to implement, compatible with different types of imaging and suitable for long-term experiments. These microwells are compatible with several surface treatments and a wide range of experimental techniques making them a powerful tool for answering key questions in cell biology. We present here a detailed protocol of the fabrication of the microwells as well as characterization of the method to ensure quality throughout the manufacturing process. These microwells support various cytoskeleton-based processes including actin polymerization, dynamic steady-state actin networks, and composite actin-microtubule networks. More broadly, they can be used to encapsulate and study over time any kind of active matter.